Methylcholanthrene-Induced Sarcomas Develop Independently from NOX2-Derived ROS - Ligtenberg, Maarten A.; Cinar, Ozcan; Holmdahl, Rikard; Mougiakakos, Dimitrios; Kiessling, Rolf (PLoS ONE, 2015)
Reactive oxygen species (ROS) produced by the inducible NADPH oxidase type 2 (NOX2) complex are essential for clearing certain infectious organisms but may also have a role in regulating inflammation and immune response. For example, ROS is involved in myeloid derived suppressor cell (MDSC)- and regulatory T cell (T(reg)) mediated T- and NK-cell suppression. However, abundant ROS produced within the tumor microenvironment, or by the tumor itself may also yield oxidative stress, which can blunt anti-tumor immune responses as well as eventually leading to tumor toxicity. In this study we aimed to decipher the role of NOX2-derived ROS in a chemically (by methylcholanthrene (MCA)) induced sarcoma model. Superoxide production by NOX2 requires the p47(phox) (NCF1) subunit to organize the formation of the NOX2 complex on the cell membrane. Homozygous mutant mice (NCF1*/*) have a functional loss of their super oxide burst while heterozygous mice (NCF1*/+) retain this key function. Mice harboring either a homo- or a heterozygous mutation were injected intramuscularly with MCA to induce sarcoma formation. We found that NOX2 functionality does not determine tumor incidence in the tested MCA model. Comprehensive immune monitoring in tumor bearing mice showed that infiltrating immune cells experienced an increase in their oxidative state regardless of the NOX2 functionality. While MCA-induced sarcomas where characterized by a T(reg) and MDSC accumulation, no significant differences could be found between NCF1*/* and NCF1*/+ mice. Furthermore, infiltrating T cells showed an increase in effector-memory cell phenotype markers in both NCF1*/* and NCF1*/+ mice. Tumors established from both NCF1*/* and NCF1*/+ mice were tested for their in vitro proliferative capacity as well as their resistance to cisplatin and radiation therapy, with no differences being recorded. Overall our findings indicate that NOX2 activity does not play a key role in tumor development or immune cell infiltration in the chemically induced MCA sarcoma model.
EVALuna2:25721